A Demonstration Study of the Quiet Time Transcendental Meditation Program - Conti, Gabriella; Doyle, Orla; Fearon, Pasco; Oppedisano, Veruska (Frontiers in Psychology, 2022)
This paper presents a demonstration study of Quiet Time (QT), a classroom-based Transcendental Meditation intervention. The aim of the study is to assess the feasibility of implementing and evaluating QT in two pilot settings in the UK and Ireland. First, teacher and pupil engagement with QT was assessed. Second, the feasibility of using a quasi-experimental design and a wide range of instruments to measure changes in pupil outcomes before and after the intervention was assessed. A wide battery of tests was included to obtain information about which might be feasible to administer and most sensitive to change. The first setting included 89 students from a London primary school: those in sixth grade received the QT intervention, while those in fifth grade practiced meditation using the Headspace application. The second setting included 100 fifth- and sixth-grade students from two schools in Ireland: one received the QT intervention, the other served as a control. Recruitment and retention rates were high in both settings, and the intervention was feasible and accepted by students, parents and teachers. Implementation fidelity was lower in the London pilot where delivery started later in the school year and the practice was affected by preparation for the Standard Assessment Tests. These results show that QT may be feasibly delivered in school settings, and suggest the use of a compact battery of tests to measure impact. The results of this demonstration study will be used to inform a larger RCT of the QT intervention.